KEPASTIAN HUKUM DALAM PENYELESAIAN SENGKETA WANPRESTASI OLEH PENGEMBANG PADA PERJANJIAN PENGIKATAN JUAL BELI (PPJB) APARTEMEN - Widjaja, Yoice Natalia; Dhoni Martien ,; Erny Kencanawati, (Journal of Innovation Research and Knowledge, 2025)
The dispute of default (wanprestasi) in Apartment Sale and Purchase Agreement (PPJB) is evident from numerous construction delays and buyer losses caused by the developer’s breach of promise (Dasein). Ideally, legal certainty should be upheld through the application of the Indonesian Civil Code (KUH Perdata) and related regulations so that the rights and obligations of the parties are fairly and securely protected (Dassollen). This raises two main issues: (1) How to resolved breach of contract disputes by developers in Apartment Sale and Purchase Agreement (PPJB)? and (2) How to ensure legal certainty in resolving breach of contract disputes by developers in Apartment Sale and Purchase Agreements (PPJB)? These questions are examined using Yahya Harahap’s Dispute Resolution Theory and Jan Michiel Otto’s Theory of Legal Certainty. The method used in this research is normative juridical research, specifically a legal library study or secondary data analysis. The legal sources include primary, secondary, and tertiary sources. The research approaches used are statute, case, conceptual, and analytical. The legal materials were collected by identifying and inventorying positive law, journals, and other legal sources. The legal materials were analyzed using grammatical, systematic, teleologis interpretations. The legal construction was carried out using analogy and argumentum a contrario methods. The result of this study is that the settlement of ppjb apartment default disputes is generally taken through litigation in court, although non-litigation options are available but rarely used and that legal certainty has been guaranteed by the Civil Code, The Flats law and the legal certainty of PPJB apartment default disputes have been regulated in the Civil Code, The Flats law, and the consumer protection law, but the implementation is still hampered by the execution of decisions, disparity in compensation, and standard clauses, so it is necessary to strengthen regulation and supervision so that consumer protection is more real.